2023
DOI: 10.2967/jnumed.122.265016
|View full text |Cite
|
Sign up to set email alerts
|

Role of18F-FDG PET/CT in Large Vessel Vasculitis and Polymyalgia Rheumatica

Abstract: Learning Objectives: On successful completion of this activity, participants should be able to (1) understand the role of 18 F-FDG PET/CT for diagnosis and therapy monitoring of LVV and PMR; (2) learn about the strengths and limitations of 18 F-FDG PET/CT in LVV and PMR, including the pitfalls;(3) know the PET procedures around LVV and PMR; and (4) realize the potential of more specific PET tracers in LVV and PMR, particularly in monitoring disease activity. Financial Disclosure: Kornelis van der Geest receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…As such, there is a clear rationale to pursue a semi-quantitative evaluation in PET imaging interpretation, although to-date there is still insufficient evidence of a superiority over visual interpretation only [ 3 , 14 ]. However, another two questions arise: (1) what is the best semi-quantitative parameter and with which separator?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, there is a clear rationale to pursue a semi-quantitative evaluation in PET imaging interpretation, although to-date there is still insufficient evidence of a superiority over visual interpretation only [ 3 , 14 ]. However, another two questions arise: (1) what is the best semi-quantitative parameter and with which separator?…”
Section: Discussionmentioning
confidence: 99%
“…18 F-2-Fluoro-2-deoxy- d -glucose ([ 18 F]FDG) positron emission tomography/computed tomography (PET/CT) has secured an important role in the diagnosis and follow-up of large vessel vasculitis (LVV) [ 1 3 ]. Current guidelines recommend a visual evaluation of [ 18 F]FDG PET with a standardized grading system based on the comparison with liver uptake, wherein uptake in a vessel equal to that of the liver is rated as possibly positive (grade 2) and uptake greater than that in the liver as definitively positive (grade 3) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these observations are in line with the recommendations put forward by van der Geest et al, who highlight the importance of evaluating multiple anatomic sites, including the shoulders, sternoclavicular joints, interspinous bursae, ischial tuberosities, hips, and greater trochanters, using 18F-FDG PET-CT to detect suspected PMR. As these authors concluded, the significant FDG uptake at multiple anatomic sites is a strong indication of PMR [42,58]. In this regard, Slart et al confirmed that 18F-FDG PET-CT is highly effective to identify inflammation in large vessels, offering precise imaging that correlates well with clinical and histopathological findings [58].…”
Section: What About Other Clinical Studies?mentioning
confidence: 99%
“…As these authors concluded, the significant FDG uptake at multiple anatomic sites is a strong indication of PMR [42,58]. In this regard, Slart et al confirmed that 18F-FDG PET-CT is highly effective to identify inflammation in large vessels, offering precise imaging that correlates well with clinical and histopathological findings [58]. Moreover, this imaging technique was also found to be very useful for detecting inflammation in characteristic areas such as the shoulders, hips, and ischial tuberosities.…”
Section: What About Other Clinical Studies?mentioning
confidence: 99%
“…18 F-FDG is the most studied PET/CT radiotracer for the diagnosis of LVV, with a sensitivity of 76 to 90% for GCA and 70-87% for TA [ 44 ]. The key imaging feature is the increased mural tracer uptake that can also help to distinguish between aortitis and periaortitis [ 45 ]. Additionally, 18 F-FDG uptake is an indicator of active disease, being a potential tool for follow-up ( Figure 3A - C )Blockmans et al .…”
Section: Vasculitismentioning
confidence: 99%